2013
DOI: 10.1039/c2cc36536g
|View full text |Cite
|
Sign up to set email alerts
|

Two-component gelation and morphology-dependent conductivity of a naphthalene-diimide (NDI) π-system by orthogonal hydrogen bonding

Abstract: The utility of an external structure-directing agent to induce orthogonal H-bonding-mediated programmed supramolecular-assembly and gelation of an n-type NDI chromophore is reported. Further, the effect of π-stacking and morphology on electrical conductivity of semiconducting NDI building blocks is revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 32 publications
1
44
0
1
Order By: Relevance
“…Three characteristic peaks due to π‐π* transition (two well resolved peaks at ≈378, ≈357 and a shoulder peak at ≈339 nm) of NDI moiety were observed in MeOH and DMSO—the intensity of the latter being significantly reduced indicating aggregation of S8 in DMSO. Close inspection of the spectra revealed that there was significant population of J‐aggregate in S8.Ant (≈20 nm red shift of the characteristic NDI peaks) whereas J‐aggregation was not evident in the case of S8.Py since the peak positions remained nearly unchanged (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three characteristic peaks due to π‐π* transition (two well resolved peaks at ≈378, ≈357 and a shoulder peak at ≈339 nm) of NDI moiety were observed in MeOH and DMSO—the intensity of the latter being significantly reduced indicating aggregation of S8 in DMSO. Close inspection of the spectra revealed that there was significant population of J‐aggregate in S8.Ant (≈20 nm red shift of the characteristic NDI peaks) whereas J‐aggregation was not evident in the case of S8.Py since the peak positions remained nearly unchanged (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Solvent dependent UV-visible spectroscopy was also performed in order to investigate the self-assembly process in S8.Ant and S8.Py.I nt hese experiments, UV-vis spectra of S8 (in MeOH and DMSO at 0.025 mm)w ere compared with that of the CT complexes. Three characteristicp eaks due to p-p*t ransition (two well resolved peaks at % 378, % 357 and as houlder peak at % 339 nm) of NDIm oiety were observed in MeOH and DMSO-the intensity of the latter being significantly reduced indicating aggregation of S8 in DMSO.C lose inspectiono ft he spectra revealed that there was significant population of J-aggregate in S8.Ant ( % 20 nm red shift of the characteristic NDI peaks) [7] whereas J-aggregation was not evidenti nt he case of S8.Py since the peak positions remained nearly unchanged (Figure 7).…”
Section: Absorption Spectroscopymentioning
confidence: 97%
See 1 more Smart Citation
“…Figure 7 shows an I – V curve taken, which showed linear behavior in the voltage range of −5 to +5 V. This linear behavior is indicative of the charge‐transfer‐induced conductive nature of the material with an observed conductivity of σ =1.9472×10 −4 S Cm −1 for a fiber of thickness of 10.89 nm. This conductive value is superior to that of conductivities observed in the case of naphthalene diimide and polythiophene assemblies 1113…”
mentioning
confidence: 56%
“…The FTIR spectrum of PLC showed peaks at 1574, 1747, and 3455 cm À1 correspondingt ot he stretchingf requencyo fC =N, C=O, and NÀHf unctional groups,r espectively.T hese peaks were respectively shiftedt o1 599( broad peak), 1730, and 3364 cm À1 in the gel phase, which suggestst hat extensive hydrogen bonding has been taken place. [7,11] The characteristicp eak of the C=O group in PBA was also shifted( from 1692 to 1701 cm À1 ), suggesting intermolecularH -bonding between the C=Og roup of PBA and the pyridine functional group of PLC (see the Supporting Information, Figure S1).…”
mentioning
confidence: 99%